Clean and Healthy Life Behavior (PHBS) of Elementary School Students Against Environmental-Based Disease Incidence in Kupang City in 2021 - Agustina AGUSTINA; Cristina EKAWATI; Wanti WANTI; Debora G. SULUH (International Journal of Environmental, Sustainability, and Social Science, 2022)
School-age is a period of vulnerability to diseases such as diarrhea, intestinal worms, caries, and anemia. This research is an analytical observational study with a cross-sectional research design with a sample of 937 elementary school students spread throughout the city of Kupang. The data analysis technique used the Chi-square test to determine the relationship between the variables studied with significant values with the help of the SPSS program. The incidence of environmental-based disease experienced by elementary school students is diarrhea and the lowest is malaria. The personal hygiene variable shows a good category, and the results of statistical tests show no relationship between personal hygiene and the incidence of environmental-based diseases. The results also show a relationship between the consumption of healthy food and the incidence of environmental-based diseases. The variable of using healthy latrines is in a good category. There is a relationship between the use of clean and healthy latrines with the incidence of environmental-based diseases. The variable presence of mosquito larvae showed free of larvae. The waste disposal variable shows that the highest level of waste disposal in the respondent's house indicates the category is not good. Hygiene variables, the presence of larvae, and waste disposal have no relationship with the incidence of environmental-based diseases in elementary school children, while the variables of healthy food consumption habits and use of latrines have a relationship with the incidence of environmental diseases. Disease-based primary school children.